Segmentation-guided and attention-enhanced GAN for SAR image restoration under multi-type interference - Xiaoyu Xu; Weiwei Fan; Jinbiao Du; Feng Zhou; Jun Sun; Maria Sabrina Greco; Fulvio Gini (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Decadal trends for aerosol in-situ optical properties and radiative forcing efficiency in a Mediterranean urban background area - Konstantinos Granakis; Maria I. Gini; Stergios Vratolis; Prodromos Fetfatzis; Martine Collaud Coen; Chris G. Tzanis; Konstantinos Eleftheriadis (Atmospheric Environment, 2026)

Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Source apportionment of PM10 particles in the urban atmosphere using PMF and LPO-XGBoost - Ying Liu; Bowen Jin; Xun Zhang; Xiansheng Liu; Tao Wang; Vy Ngoc Thuy Dinh; Jean-Luc Jaffrezo; Gaëlle Uzu; Pamela Dominutti; Sophie Darfeuil; Olivier Favez; Sébastien Conil; et al. (Environmental Research, 2025)

Dosimetry simulations of ultrafine particles deposition to the human respiratory tract and transport to the olfactory region for female receptors - Eleftheria Chalvatzaki; Sofia Eirini Chatoutsidou; Lila Diapouli; Maria I. Gini; Manousos I. Manousakas; Evangelia Samoli; Kostas Eleftheriadis; Mihalis Lazaridis (Atmospheric Environment, 2025)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

On the relation between the planetary boundary layer height and in situ surface observations of atmospheric aerosol pollutants during spring in an urban area - Romanos Foskinis; Maria I. Gini; Panagiotis Kokkalis; Evangelia Diapouli; Stergios Vratolis; Konstantinos Granakis; Olga Zografou; Mika Komppula; Ville Vakkari; Athanasios Nenes; Alexandros Papayannis; Konstantinos Eleftheriadis (Atmospheric Research, 2024)

Characterisation of urban aerosol size distribution by radiocarbon and PIXE analyses in a middle-European urban environment for source identification: a pilot study - Anikó Angyal; Zoltán Szoboszlai; István Major; Mihály Molnár; Tamás Varga; Zsófia Török; Enikő Papp; Furu Enikő; Maria Gini; Manousos Ioannis Manousakas; Zita Szikszai; Zsófia Kertész (Environmental Science and Pollution Research, 2024)
This study, conducted in Debrecen, Hungary, aimed to analyse atmospheric particulate matter (APM or PM) through radiocarbon and PIXE analyses during the winter smog (23–25 January) and spring (15–18 May) seasons. The information presented in this pilot study aims to provide insight into the importance of utilising detailed characteristics of the mass size distributions of fossil carbon (f f ) and contemporary carbon (f C ) content. Additionally, it seeks to compare these characteristics with the size distributions of various elements to enable even more accurate PM source identification. In winter, APM concentrations were 86.27 μg/m 3 (total), 17.07 μg/m 3 (f C ) and 10.4 μg/m 3 (f f ). In spring, these values changed to 29.5 μg/m 3 , 2.64 μg/m 3 and 7.01 μg/m 3 , respectively. Notably, differences in mass size distribution patterns were observed between the two seasons, suggesting varied sources for contemporary carbon. Biomass burning emerged as a crucial source during the smog period, supported by similar MMAD (Mass Median Aerodynamic Diameter) values and a strong correlation ( r = 0.95, p < 0.01) between potassium and f C. In spring, a significant change in the concentration and distribution of f C occurred, with a broad, coarse mode and a less prominent accumulation mode. F f was found to have similar distributions as PM, with nearly the same MMADs, during both periods. Finally, a comprehensive comparison of modal characteristics identified specific sources for the various components, including biomass burning, vehicle exhaust, coal and oil combustion, vehicle non-exhaust, road dust, tyre abrasion, mineral dust and biogenic emission. This study showcases how using radiocarbon and PIXE analysis in size distribution data can enhance our understanding of the sources of PM and their effects on different size fractions of PM.

Wildfire and African dust aerosol oxidative potential, exposure and dose in the human respiratory tract - Maria Mylonaki; Maria Gini; Maria Georgopoulou; Marika Pilou; Eleftheria Chalvatzaki; Stavros Solomos; Evangelia Diapouli; Elina Giannakaki; Mihalis Lazaridis; Spyros N. Pandis; Athanasios Nenes; Konstantinos Eleftheriadis; et al. (Science of The Total Environment, 2024)

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Long-range transported biomass-burning aerosols from large-scale wildfires in Russia and surrounding regions with respect to radioactive tracers - Ekaterini Dalaka; Maria I. Gini; Evangelia Diapouli; Konstantinos Eleftheriadis (Air Quality, Atmosphere & Health, 2019)

Long Term Flux of Saharan Dust to the Aegean Sea around the Attica Region, Greece - Vasiliki Vasilatou; Manousos Manousakas; Maria Gini; Evangelia Diapouli; Michael Scoullos; Konstantinos Eleftheriadis (Frontiers in Marine Science, 2017)